HIV, sexual risk, and ethnicity among men in England who have sex with men. Issue 6 (30th November 2004) - Hickson, F; Reid, D; Weatherburn, P; Stephens, M; Nutland, W; Boakye, P
Abstract : Objectives: To examine ethnic group differences in HIV testing history and sexual HIV risk behaviours that may account for such differences, among men in England who have sex with men (MSM), in order to inform HIV prevention planning priorities. Methods: A self completion survey in the summer of 2001 was carried out in collaboration with community based health promoters. Three recruitment methods were used: "gay pride" festivals, health promoter distributed leaflets, internet version advertised with gay service providers. The leaflet was produced with an alternative cover for targeted recruitment of black men. Results: In a sample of 13 369 MSM living in England, 17.0% were from minority ethnic groups and 5.4% had tested HIV positive. Compared to the white British majority, Asian men were 0.32 times as likely to be living with diagnosed HIV infection, while black men were 2.06 times as likely to be doing so. Among men who had not tested HIV positive, Asian men were less likely to have sex with a known HIV positive partner, while black men were more likely to have insertive unprotected anal intercourse both with a partner they knew to be HIV positive and with a partner whose HIV status they did not know. Conclusions: Among MSM in England, HIV prevalence is higher among black men and lower among Asian men compared with the white British majority. Increased sexual HIV risk behaviour, especially exposure during insertive anal intercourse, accounts for some of this difference. HIV prevention programmes for MSM and African people should both prioritise black MSM.